2011
DOI: 10.1016/j.jmoldx.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Development and Clinical Implementation of a Combination Deletion PCR and Multiplex Ligation-Dependent Probe Amplification Assay for Detecting Deletions Involving the Human α-Globin Gene Cluster

Abstract: The ␣-thalassemias are a group of hereditary disorders caused by reduced synthesis of the ␣-chain of hemoglobin. We have developed and tested an ␣-thalassemia assay that uses both multiplex ligationdependent probe amplification (MLPA) with Luminex-based detection and deletion PCR technologies. The MLPA assay consisted of 20 probes, 15 of which hybridized to the ␣-globin gene cluster and 5 that served as control probes. A PCR assay was developed to confirm the presence of heterozygous/homozygous 3.7-kb and 4.2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 18 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Several methods have been developed to identify unknown deletions and duplications in the α-globin genes, using quantitative real-time PCR (real-time qPCR) assays [ 13 - 15 ] or multiplex ligation-dependent probe amplification (MLPA) assays [ 16 , 17 ]. Here, we describe a fast, robust and specific method, designated HBA-CNV, that measures copy number variation using real-time qPCR.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed to identify unknown deletions and duplications in the α-globin genes, using quantitative real-time PCR (real-time qPCR) assays [ 13 - 15 ] or multiplex ligation-dependent probe amplification (MLPA) assays [ 16 , 17 ]. Here, we describe a fast, robust and specific method, designated HBA-CNV, that measures copy number variation using real-time qPCR.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the closely related MLPA, which requires about 20 hours to complete, the MOL-PCR assay can be performed very rapidly 4 . MLPA remains, even in the version adapted to the microsphere array and when using the same detection platform as MOL-PCR, tedious due to the number of steps or necessity for overnight hybridization 34 . The MOL-PCR assay is designed to be performed in 96-well plates, while simultaneously allowing each well to be screened for up to 50 markers, and provides high-confidence results within 6 h 6,12 .…”
Section: Resultsmentioning
confidence: 99%
“…2 The MLPA results revealed that the deleted regions expanded from 3.5 kb upstream HBZ to 0.2 kb downstream HBA1 (20 probe) in the two unrelated patients P6 and P7. Whereas the deleted regions expanded from 3.5 kb upstream HBZ to 0.5 kb downstream HBA1 (21 probe) in patient 16 (a, b) et al [10] reported a study comparing MLPA and SB Analysis in a-thalassemia and emphasized the importance of MLPA in defining patogenic mutations as a complimentary method to SB, rather than a stand alone technique. Colosimo et al [8] also identified MLPA as an effective method for screening a-thalassemia mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of testing strategies have been used to detect deletions and mutations within the a-globin gene cluster, including Reverse Dot-Blot Hybridisation (RDB), Southern blot (SB), Gap-PCR, multiplex ligation dependent probe amplification (MLPA) and sequence analysis [8][9][10]. Since the MLPA technique was first described by Schouten et al [14], many centers have used this method to identify the a-globin gene cluster deletions [11].…”
Section: Introductionmentioning
confidence: 99%